COMPARISON STUDY OF BRACING CONFIGURATION WITH SHEAR LINK IN ECCENTRICALLY BRACED FRAME STEEL STRUCTURE - Jusuf Wilson Meynerd Rafael; Alva Yuventus Lukas (Universitas Islam Malang, 2020)
The EBF structural system is identified by the use of bracing and link beams as components that work to receive lateral seismic loads. The position of the link beam makes the EBF system have several choices of bracing configuration; D-Braces, Split K-Braces, V-Braces, Split K & Inverted Split K-Braces, Inverted Y-Braces. Structural analysis was carried out on a 10-story building model for the EBF system with different type of bracing configurations using the ETABS software. All models analyzed according to Indonesian Code (SNI 1729:2015 and SNI 1726:2019) to obtain the structural element. Seismic analysis uses the response spectrum analysis method to obtain the structural response parameters in the EBF system. Result of the analysis for all of bracing configuration are shown that Split K-Braces model has the best response parameters when compared to the MRF system. The lowest value for the parameter is owned by Inverted Y-Braces, although overall it is still larger than the MRF system. The bracing configuration greatly affects the response of EBF system due to the behavior that occurs in the link beam, therefore the selection for type of bracing configuration is also important in the EBF system structure design.